2018
DOI: 10.1017/s0022149x18000056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data confirm the taxonomic position of Hymenolepis erinacei (Cyclophyllidea: Hymenolepididae) and host switching, with notes on cestodes of Palaearctic hedgehogs (Erinaceidae)

Abstract: The cestode Hymenolepis erinacei is regarded as a widely distributed parasite in European hedgehogs of the genus Erinaceus, although the taxonomic position of this hymenolepidid has been debated for a considerable period of time. We present the first molecular data for this cestode, including partial DNA sequences of mitochondrial 16S and nuclear 28S ribosomal genes. Molecular phylogenetic analysis clusters H. erinacei in one clade together with representatives of the genus Hymenolepis from rodents. Characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The tapeworm species H. diminuta was previously reported in the A. sylvaticus mouse population from St Kilda ( Morton-Boyd, 1959 ). However, species identification of helminth parasites by morphology can be challenging, not least in the case of Hymenolepis sensu lato ( Makarikov and Tkach, 2013 ; Binkienė et al, 2018 ). Biochemical, growth and behavioural studies suggest that H. hibernia and H. diminuta are genetically distinct, with H. hibernia being adapted to Palaearctic mice from the genus Apodemus , whereas H. diminuta is a rat tapeworm ( Montgomery et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tapeworm species H. diminuta was previously reported in the A. sylvaticus mouse population from St Kilda ( Morton-Boyd, 1959 ). However, species identification of helminth parasites by morphology can be challenging, not least in the case of Hymenolepis sensu lato ( Makarikov and Tkach, 2013 ; Binkienė et al, 2018 ). Biochemical, growth and behavioural studies suggest that H. hibernia and H. diminuta are genetically distinct, with H. hibernia being adapted to Palaearctic mice from the genus Apodemus , whereas H. diminuta is a rat tapeworm ( Montgomery et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…To build a phylogenetic tree and reconstruct relationships between the R. asymmetrica and other hymenolepidids, we used maximum likelihood with a general time reversible model as distance substitution. For phylogenetic analyses, we used 5 newly obtained nucleotide sequences of R. asymmetrica and those of hymenolepidids published in previous studies outlined in table 2 (Lockyer et al, 2003;Waeschenbach et al, 2007;Haukisalmi et al, 2010;Greiman & Tkach, 2012;Tkach et al, 2013;Widmer et al, 2013;Makarikov et al, 2015;Nkouawa et al, 2016;Binkienė et al, 2019;Haas et al, 2020). Dilepis undula (Schrank, 1788) was used as an outgroup as proposed by Neov et al (2019) for the phylogeny of Hymenolepididae.…”
Section: Methodsmentioning
confidence: 99%
“…The pioneer study by Haukisalmi et al (2010) proposed the first phylogenetic hypothesis for the relationships among mammalian hymenolepidids, which was based on sequencing partial (D1-D3) 28S ribosomal RNA (rRNA) gene; it revealed the presence of four major phyletic lineages in the group, which were named 'Ditestolepis clade', 'Arostrilepis clade', 'Hymenolepis clade' and 'Rodentolepis clade'. Subsequently, Neov et al (2019) analysed the phylogenetic relationships of this group based on partial (D1-D3) 28S rRNA gene of 12 selected taxa as well as sequences obtained by Haukisalmi et al (2010) and other authors (Greiman & Tkach, 2012;Greiman et al, 2013;Tkach et al, 2013Tkach et al, , 2018Binkienė et al, 2015Binkienė et al, , 2019Makarikov et al, 2015Makarikov et al, , 2018, comprising a total of 40 taxa. This study confirmed the same major clades but also added more details on the evolution of the host-parasite associations and the main morphological characteristics of the members of this group.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) analysed the phylogenetic relationships of this group based on partial (D1–D3) 28S rRNA gene of 12 selected taxa as well as sequences obtained by Haukisalmi et al . (2010) and other authors (Greiman & Tkach, 2012; Greiman et al ., 2013; Tkach et al ., 2013, 2018; Binkienė et al ., 2015, 2019; Makarikov et al ., 2015, 2018), comprising a total of 40 taxa. This study confirmed the same major clades but also added more details on the evolution of the host–parasite associations and the main morphological characteristics of the members of this group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation